إدارة المعرفة ودورها في تحقيق الإبداع في المؤسسات الصغيرة والمتوسطة في الجزائر - بن وسعد, زينة; بوزيان الرحماني, هاجر (جامعة الوادي - University of Eloued, 2018)
تهدف هذه الورقة البحثية إلى التعرف على دور إدارة المعرفة في تحقيق الإبداع في المؤسسات الصغيرة والمتوسطة، هذه المؤسسات التي أصبحت تمثل أكثر من 90 % من النسيج الاقتصادي لكلّ من الدول المتقدمة والنامية على حد سواء، وأصبح من الضروري عليها تبني أساليب تسيير حديثة في إدارتها حتى تصل إلى درجة التميز وتتمكن بالتالي من الصمود أمام المنافسة. أظهرت نتائج هذه الدراسة أنّ استعمال إدارة المعرفة يعتبر ضرورة حتمية بالنسبة للمؤسسات الصغيرة والمتوسطة، وذلك لأنّ هذه الطريقة تساعد على الكشف عن المعارف الداخلية والخارجية، الصريحة والضمنية، وتندد بضرورة تشجيع العمل الجماعي، والتشارك فيه، ممّا يعزز روح الإبداع في العمليات وفي الإنتاج على حد سواء. تعاني المؤسسات الصغيرة والمتوسطة من مشكل عدم إمكانية تبنيها لنظام إدارة المعرفة بشكله الصحيح نظرا للعديد من المعوقات والتي تتمثل أساسا في محدودية إمكانياتها المالية، نقص الخبرة والكفاءات العاملة بها، سياسة التوظيف العائلي التي تغلب عليها This paper aims to identify the role of knowledge management in achieving innovation in small and medium enterprises. These institutions represent more than 90% of the economic of both developed and developing countries. It is necessary for them to adopt modern management methods in their management for reach the level of excellence and thus be able to withstand the competition. The results of this study show that the use of knowledge management is an imperative for SMEs, because this method helps to detect internal and external, explicit and implicit knowledge, and denotes the need to encourage and share teamwork, which promotes the spirit of creativity in processes and production to the extent whether. Small and medium enterprises suffer from the problem of not being able to adopt the knowledge management system properly due to many obstacles, which are mainly limited in their financial capacities, lack of experience and competencies working in them, …
Knowledge management and its role in achieving innovation in small and medium enterprises in Algeria
مقال
Keywords: إدارة المعرفة، الإبداع، المؤسسات الصغيرة والمتوسطة; knowledge management, creativity, small and medium enterprises.